Causal impacts of family planning support for vulnerable households - Veldhoven, Anouk van (International Journal of Population Data Science, 2026)
There is ample evidence of low contraceptive uptake and unmet need for family planning by mentally vulnerable individuals. While avoiding unwanted pregnancies for this group may be especially important to improve their (mental) wellbeing, autonomy and self-reliance, impacts of family planning support specifically targeted at mentally vulnerable groups in high-income countries are understudied, with only a few small-scale studies that pilot and qualitatively indicate that family planning counselling is positively received by vulnerable individuals. I study the effects of family planning counselling on its intended outcomes: contraceptive uptake, pregnancies, and households’ socio-economic outcomes that enhance a stable, supportive home for children. To this end, I evaluate the causal impacts of a nation-wide family planning support program in the Netherlands named Nu Niet Zwanger (“Not pregnant now”). The program offers professional training to equip local healthcare professionals and social workers with the skill to respectfully initiate conversations about family planning with clients and, if desired, provide support to access suitable contraceptive methods. The program is implemented by regional public health offices, and was rolled out gradually across Dutch municipalities since 2018. As of November 2025, 90% of all municipalities are implementing the program. Assuming that the timing of adoption of the program by municipalities is random and unrelated to residents’ outcomes, I estimate causally identified effects in a difference-in-differences design, linking national population-wide data from Statistics Netherlands over the period 2015-2024 to program implementation data collected from the regional public health offices project teams.